ANALISIS PENGARUH INFORMASI NON KEUANGAN, INFORMASI KEUANGAN, DAN OWNERSHIP TERHADAP UNDERPRICING PADA PERUSAHAAN NON KEUANGAN YANG MELAKUKAN INITIAL PUBLIC OFFERING (IPO) DI BEI PERIODE 2008-2014 - Firmanah, Dhani Utary; Muharam, Harjum (Faculty of Economics and Business Diponegoro University, 2015)
This study aims to analyze the influece of the non-financial information (underwriter reputation and firm size), the financial information (Return on Assets, Debt to Equity Ratio and Earning Per Share), and the ownership (retained shares by owner and foreign ownership) on underpricing at non-financial companies in Indonesia Stock Exchange during 2008-2014. The population in this study consists of all IPO non-financial firm in Indonesia Stock Exchange for the period 2008-2014. After passed the purposive sampling method there were 77 non-financial companies obtained as sample. The data analysis methods used is multiple linier regression analysis and with the classical assumption test. The result of this research showed that underwriter reputation, Return 0n Assets (ROA) and Earning Per Share (EPS) have a negative and significant effect to underpricing, Debt to Equity Ratio (DER) has a positive and significant effect to underpricing, while firm size, retained shares by owner and foreign ownership have no significant effect to underpricing.